Analysis and Study of the Effect of Atmospheric Turbulence on Laser weapon in Iraq (Baghdad Science Journal, 2025)
One of the most important challenges facing the development of laser weapons is represented by the attenuation of the laser beam as it passed through the layers of atmosphere.This paper presents a theoretical study to simulate the effect of turbulence attenuation and calculates the decrease of laser power in Iraq. The refractive index structure C_n^2 is very important parameter to measure the strength of the atmospheric turbulence, which is affected by microclimate conditions, propagation path, season and time in the day. The results of measurements and predictions are based on the Kolmogorov turbulence theory. It was demonstrated by simulations that the laser weapons in Iraq were severely affected due to the large change in temperatures, the limited effective range of laser weapon to a few kilometers as a result of high attenuation and the middle of stratosphere considered as a homogeneous and a suitable area for the work of laser weapons, so be a favorite area of fighter aircraft.